Proyecciones de clima para el periodo 2011-2040 en el África subsahariana occidental y su impacto en la agricultura de la región - Gallardo Andrés, Clemente; Ruiz Ramos, Margarita; Sánchez Sánchez, Enrique (UNISCI Discussion Papers, 2007)
The results of 12 AOGCMs (Atmospheric-Oceanic Global Climate Models) available at WCRP CMIP3 multimodel database have been used to analyze the climatic projections under SRES-A2 emissions scenario for the period 2011-2040. There are not many studies focused on this period, but it is essential to develop strategies on short and medium range, such as the ones needed for migration issues. The results obtained indicate temperature increases around 1 degree for the West Sub-Saharan Africa region. The trend for precipitation is towards a slight increase over most of the areas. Both factors imply a slight increase in aridity over the coastal areas from Senegal to Cameroon, and a decrease over the inland areas of the region. As a consequence of these projections a decrease in agricultural yield is dominant over the most of the region.